Zooplankton Biomass Depletion Event Reveals the Importance of Small Pelagic Fish Top-Down Control in the Western Mediterranean Coastal Waters - Yebra, Lidia; Espejo, Estefanía; Putzeys, Sébastien; Giráldez, Ana; Gómez-Jakobsen, Francisco; León, Pablo; Salles, Soluna; Torres, Pedro; Mercado, Jesús M. (Frontiers in Marine Science, 2020)
The influence of hydrochemistry and trophic conditions on the coastal zooplankton community's biomass and metabolic activities was investigated along the Spanish Mediterranean coastal waters, from Algeciras Bay to Barcelona, from autumn 2011 to autumn 2012. Two hydrographic regions were differentiated: NW Alboran (ALB) and W Mediterranean (MED). Zooplankton metabolism was assessed from measurements of the electron transport system (ETS) and aminoacyl-tRNA synthetases (AARS) activities, as proxies for potential respiration and somatic growth, respectively. Zooplankton showed 3 to 5-fold higher biomass in ALB than in MED during autumn 2011 and spring 2012. However, in autumn 2012 a drastic decrease in biomass standing stock was observed in ALB, with no significant differences between the two regions. This biomass depletion event was not associated with environmental variables, food availability or zooplankton metabolic rates, but coincided with a 2-fold peak of Sardina pilchardus landings in ALB. A reduced standing stock coupled with high zooplankton growth rates suggests mortality by predation as the main cause for the low zooplankton biomass typically observed in MED, and in ALB during autumn 2012.